Divergent Approach to the Synthesis of 2-Aryl-5-(thiophen-2-yl)-1,3,4-oxadiazoles and -1,3,4-thiadiazoles - Samsonenko, Anna L.; Kostyuchenko, Anastasia S.; Zheleznova, Tatyana Y.; Uliankin, Evgenii B.; Chernenko, Sergei A.; Shuvalov, Vladislav Y.; Shatsauskas, Anton L.; Fisyuk, Alexander S. (Synlett, 2025)
The reaction of 2-(chloromethyl)-1,3,4-thiadiazoles and -1,3,4-oxadiazoles with thioacetic acid in the presence of DIPEA led to the formation of S-[(1,3,4-thiadiazol-2-yl)methyl]- and [(1,3,4-oxadiazol-2-yl)methyl]ethanethioate. A series of 2-thienyl-substituted 1,3,4-oxadiazoles and 1,3,4-thiadiazoles were obtained by the reaction of 3-chloroacrylaldehydes with (1,3,4-thiadiazol-2-yl)- and (1,3,4-oxadiazol-2-yl)methanethiols formed in situ from S-[(1,3,4-thia(oxa)diazol-2-yl)methyl]ethanethioate in methanol in the presence of K2CO3. The photophysical properties of the synthesized compounds were studied.
Keywords: 3-chloroacrylaldehydes; 1,3,4-oxadiazoles; 1,3,4-thiadiazoles; divergent synthesis; heterocycles